The Influence of Social Support, Self-Esteem, and Optimism on Resilience of High School Students During the Covid-19 Pandemic - Sari, Sindi Pratika; Alfiasari, Alfiasari (Department of Family and Consumer Sciences, Faculty of Human Ecology, IPB University, 2024)
Resilience is an important thing that adolescents should have in dealing with changes during the Covid-19 pandemic. The purpose of this study is to analyze the influence of social support, self-esteem, and optimism on high school student resilience during the Covid-19 pandemic. The research design used is explanatory with voluntary sampling techniques and involves 193 high school students in the Kebumen regency, data analysis was performed using descriptive and inferential analysis used SPSS and Microsoft Excel. The results showed that children get the highest social support from parents and the lowest from teachers. In addition, the largest proportion of students have moderate self-esteem and resilience. However, the largest proportion for optimism is in a low category. The results also showed a very significant positive relationship between social support, self-esteem, and optimism with high school students' resilience. The other result also shows that high school students' resilience during the Covid-19 pandemic was directly affected by self-esteem and optimism. Variables of social support, self-esteem, optimism, adolescent and family characteristics are important aspects in improving the resilience of high school students during the Covid-19 pandemic.